Hair Follicle Morphogenesis During Embryogenesis, Neogenesis, and Organogenesis - Park, Sangbum (Frontiers in Cell and Developmental Biology, 2022)
Hair follicles are mini organs that repeat the growth and regression cycle continuously. These dynamic changes are driven by the regulation of stem cells via their multiple niche components. To build the complex structure of hair follicles and surrounding niches, sophisticated morphogenesis is required during embryonic development. This review will explore how hair follicles are formed and maintained through dynamic cellular changes and diverse signaling pathways. In addition, comparisons of differences in stem cells and surrounding niche components during embryogenesis, neogenesis, and organogenesis will provide a comprehensive understanding of mechanisms for hair follicle generation and insights into skin regeneration.